Ultimate hull-girder-strength-based reliability of a double-hull oil tanker after collision in the Adriatic Sea. (13th March 2017) - Parunov, Joško; Rudan, Smiljko; Ćorak, Maro
ABSTRACT: The aim of this paper is to present a methodology for the assessment of the structural reliability of an oil tanker damaged in a hypothetical collision accident in the Adriatic Sea. Monte Carlo simulation is employed to generate random damage scenarios. Assumption of the damage size is based on the numerical simulation of the ship–ship collision. Residual ultimate strength and still-water bending moment distribution are determined based on the size and location of the damage. Structural reliability analysis is employed to determine the safety index with respect to the ultimate hull-girder failure. Histograms of safety indices are thus obtained, representing new measures for the performance assessment of the damaged ship. If extended to more severe design wave environments and collision scenarios, the presented methodology may be used for general reliability-based comparison of different alternative designs of marine structures with respect to the accidental failure modes or for improvement of ship structural design rules.